2019
DOI: 10.3390/v11050424
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Surveillance for Poliovirus and Other Enteroviruses: Long-Term Experience in Moscow, Russian Federation, 2004–2017

Abstract: Polio and enterovirus surveillance may include a number of approaches, including incidence-based observation, a sentinel physician system, environmental monitoring and acute flaccid paralysis (AFP) surveillance. The relative value of these methods is widely debated. Here we summarized the results of 14 years of environmental surveillance at four sewage treatment plants of various capacities in Moscow, Russia. A total of 5450 samples were screened, yielding 1089 (20.0%) positive samples. There were 1168 viruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 38 publications
4
33
0
1
Order By: Relevance
“…Thus, one would expect that in Russia there may be patients continuously or chronically excreting polioviruses. The validity of this assumption is evidenced by the fact that the significantly divergent poliovirus type 2 (17.6% nt substitutions in VP1) was detected in Moscow wastewater [60]. Our current observation confirms the danger of the prolonged excretion of poliovirus by persons with immunodeficiency conditions, and the need for surveillance for iVDPV.…”
Section: Importance For Surveillance Of Poliovirus Circulationsupporting
confidence: 79%
“…Thus, one would expect that in Russia there may be patients continuously or chronically excreting polioviruses. The validity of this assumption is evidenced by the fact that the significantly divergent poliovirus type 2 (17.6% nt substitutions in VP1) was detected in Moscow wastewater [60]. Our current observation confirms the danger of the prolonged excretion of poliovirus by persons with immunodeficiency conditions, and the need for surveillance for iVDPV.…”
Section: Importance For Surveillance Of Poliovirus Circulationsupporting
confidence: 79%
“…The composition of subtypes detected in the environmental waters in the present study reflects the circulation of HEV strains in humans and animals in the same region. Previous reports from other countries also demonstrated a correlation between detected viruses in wastewater and clinical cases (Hellmér et al 2014;Ivanova et al 2019).…”
supporting
confidence: 59%
“…Similarly, a previous study [ 56 ] reported the silent circulation of echovirus 30 in the environment before the onset of a large outbreak of AM accounted in 2009 in Finland. However, a study conducted in Russia [ 57 ], failed in associating clinical and environmental isolates of echovirus 30 in the same temporal and geographical scenario, reporting echovirus 30 almost exclusively from medical diagnosis of AM. This emphasizes the use of highly sensitive and effective methods to unveil the complex diversity of EVs in environmental samples when wastewater-based epidemiology approaches are conducted.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of reports of AM linked to echovirus 30 in Argentina since 2012 made it impossible for us to compare the characterized environmental strains with contemporaneous clinical isolates. A link between environmental and clinical isolates of different EVs obtained in the same temporal and geographical range has been extensively documented [ 57 , 58 , 59 ]. Nevertheless, our study suggests that echovirus 30 strains detected in the environment of a specific location could predict future epidemics beyond local boundaries.…”
Section: Discussionmentioning
confidence: 99%